Enhancement of Losartan Transdermal Transport Through Incorporation into Chitosan Nanoparticles - Efiana, Nuri Ari; Nugroho, Akhmad Kharis; Martien, Ronny (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Losartan, an antihypertensive agent, has low oral bioavailability. Therefore, developing a design for transdermal delivery of losartan is interesting. This study aims to enhance losartan in vitro transport by incorporating it into chitosan nanoparticles. Transdermal transport studies were conducted using two experimental groups: the pretreatment group using oleic acid and propylene glycol, and the group without pretreatment. The results showed that losartan incorporated into chitosan nanoparticles resulted in a significantly higher amount of drug being transported than the losartan solution (control) in both experimental groups. In the experiment without pretreatment, the amount of losartan from the control could not be detected in the receptor compartment until 28 hours. In contrast, losartan was detected at 16 hours of transport from chitosan nanoparticles. In pretreatment, chitosan nanoparticles exhibited 6.6fold higher losartan transport than the control. In addition, losartan chitosan nanoparticles showed significant increases in steady-state flux and transport efficiency by 3.3 and 6.6 times higher than the control, respectively. It can be concluded that the incorporation of losartan into chitosan nanoparticles can increase its transdermal transport.